2015
DOI: 10.3174/ajnr.a4494
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of the Hypoglossal Nerve in the Neck: Visualization and Initial Clinical Experience with Patients

Abstract: BACKGROUND AND PURPOSE:The hypoglossal nerve, providing motor innervation for the tongue, can be affected in many diseases of the neck and skull base, leading to dysarthria, dysphagia, and ultimately atrophy of the tongue. We determined the feasibility of direct visualization of the hypoglossal nerve in the neck with ultrasound, testing this technique on healthy volunteers and evaluating it in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Jean suggested that the main motor nuclei involved in swallowing motor activity are the hypoglossal nucleus, and the nucleus ambiguus, hypoglossal, glossopharyngeal, and trigeminal nerves are the main motor nerves [ 48 ]. A lesion of the hypoglossal nerve can cause dysarthria, dysphagia, and tongue paralysis [ 49 ]. Sundman et al suggested that the three mechanisms underlying dysphagia were delayed initiation of the swallowing reflex, impaired pharyngeal muscle function, and impaired coordination [ 50 ]; these symptoms of dysphagia are attributed to the damage of several central nuclei associated with swallowing [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jean suggested that the main motor nuclei involved in swallowing motor activity are the hypoglossal nucleus, and the nucleus ambiguus, hypoglossal, glossopharyngeal, and trigeminal nerves are the main motor nerves [ 48 ]. A lesion of the hypoglossal nerve can cause dysarthria, dysphagia, and tongue paralysis [ 49 ]. Sundman et al suggested that the three mechanisms underlying dysphagia were delayed initiation of the swallowing reflex, impaired pharyngeal muscle function, and impaired coordination [ 50 ]; these symptoms of dysphagia are attributed to the damage of several central nuclei associated with swallowing [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance is described as being the best imaging method for assessing the extracranial segment of the hypoglossal nerve, but it is limited by small nerve sizes [25]. Nevertheless, one study proposed an imaging protocol for the nerve visualization using ultrasound applied on healthy volunteers and patients [14]. The correct identification of the nerve was also confirmed, in the same study, by ultrasound guided ink injections and dissection of cadaveric specimens.…”
Section: The Hypoglossal Nervementioning
confidence: 95%
“…Moreover, cranial nerves received less attention compared to peripheral nerves [9]. Currently, reference values for cranial nerves in healthy volunteers were reported only by a few articles [10][11][12][13][14].…”
Section: Background and Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Nevertheless, both nerves can be localized with standard diagnostic ultrasound (US) equipment. 20,21 We hypothesized that both could also be stimulated percutaneously under US guidance, and we recently published results of an acute neurostimulation experiment in patients with OSA. 10 Here we describe in detail procedural techniques and equipment for successful nerve localization and stimulation.…”
mentioning
confidence: 99%